2020
DOI: 10.26452/ijrps.v11ispl2.2174
|View full text |Cite
|
Sign up to set email alerts
|

Correlation With Disease Activity Score 28 (Das28) With Pulmonary Function Test In Rheumatoid Arthritis Patients

Abstract: Rheumatoid Arthritis (RA) is a chronic inflammatory disease of unknown etiology involving both small and large joints with many extra-articular manifestations. There may be a variety of pulmonary complications associated with RA based on its disease activity and levels of RF and anti-CCP titers. Pulmonary involvement may be seen at different levels of the respiratory system, with infection being the most common cause of mortality. Our study shows the association and degree of pulmonary involvement in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Human medicine studies of diseases affected by biofilms such as cystic fibrosis have shown the isolated Streptococcus pneumoniae strains have higher biofilm formation capacity and their MBIC are higher than MIC compared to strains from blood-cultures that have lower biofilm formation capacity and MBIC lower than MIC for various antimicrobials (García-Castillo et al, 2007). In addition to antimicrobials, lower MBIC than MIC values can be obtained using various natural products against multi-drug resistant Klebsiella pneumoniae (Magesh et al, 2013) or vitamin C against Streptococcus mutans (Eydou et al, 2020). Studies in human medicine have shown the correlation of biofilm formation capacity with multidrug resistance to vary between bacterial species and antimicrobial agents (Ramos-Vivas et al, 2019;Cepas et al, 2019).…”
Section: Biofilm Producingmentioning
confidence: 99%
“…Human medicine studies of diseases affected by biofilms such as cystic fibrosis have shown the isolated Streptococcus pneumoniae strains have higher biofilm formation capacity and their MBIC are higher than MIC compared to strains from blood-cultures that have lower biofilm formation capacity and MBIC lower than MIC for various antimicrobials (García-Castillo et al, 2007). In addition to antimicrobials, lower MBIC than MIC values can be obtained using various natural products against multi-drug resistant Klebsiella pneumoniae (Magesh et al, 2013) or vitamin C against Streptococcus mutans (Eydou et al, 2020). Studies in human medicine have shown the correlation of biofilm formation capacity with multidrug resistance to vary between bacterial species and antimicrobial agents (Ramos-Vivas et al, 2019;Cepas et al, 2019).…”
Section: Biofilm Producingmentioning
confidence: 99%